Jerat Pinjol di Kalangan Gen Z Bingkai Perspektif Islam dan Perlindungan Konsumen - Priyanto, Toni; Indriani, Susi; Fauzi, Ilham (LPPAIK Universitas Muhammadiyah Bandung, 2025)
The phenomenon of online loans has become a significant issue in Indonesia, especially for Generation Z who are adaptive to digital technology. This study aims to review the literature related to the impact of these two phenomena on the economic welfare of Generation Z, by reviewing aspects of compliance with Islamic economic principles and consumer protection. This type of research is a qualitative literature study using the Systematic Literature Review (SLR) method based on the PRISMA framework. This method is used to analyze trends, gaps, and research opportunities in this field. The results show the importance of financial literacy, sharia-based regulations, and consumer protection mechanisms in reducing the negative impacts and maximizing the benefits of digital financial technology.